Remaking New York : primitive globalization and the politics of urban community - Sites, William (Minneapolis : University of Minnesota Press, 2003)
Inequality increases, instability grows, communities fragment: this is the fate of a city in the wake of globalization--but is globalization really the cause? Proposing a new perspective on politics, globalization, and the city, this provocative book argues that such urban problems result in part from U.S. policies that can be changed. William Sites develops the concept of primitive globalization, identifying a pattern of reactive politics--ad hoc measures to subsidize business, displace the urban poor, and dismantle the welfare state--that uproots social actors (corporations, citizens, urban residents) and facilitates a damaging, short-term-oriented type of international integration. In light of this theory, Sites examines the transformation of New York City since the 1970s, focusing on the logic of political action at national, local, and neighborhood levels. In the process, the story of late twentieth-century New York and its Lower East Side community emerges as something different: not a taleof globalist transformation or of local resurgence but a distinctly American case, one in which urban politics and the state, in their own right, exacerbate inequality and community fragmentation within the city.
Primitive globalization? -- Building an urban neoliberalism -- Public action -- Urban movements, local control -- Beyond primitive globalization.
Revision of the author's thesis (doctoral--New York University).
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: City planning -- New York (State) -- New York; Community development -- New York (State) -- New York; Community organization -- New York (State) -- New York; Political participation -- New York (State) -- New York; Municipal government -- New York (State) -- New York; Globalization; New York (N.Y.) -- Politics and government; New York (N.Y.) -- Economic policy; Lower East Side (New York, N.Y.) -- Social conditions; Lower East Side (New York, N.Y.) -- Economic conditions; Urbanisme -- New York (État) -- New York; Organisation communautaire -- New York (État) -- New York; Participation politique -- New York (État) -- New York; Mondialisation; Développement communautaire -- New York (État) -- New York; New York (N.Y.) -- Administration; New York (N.Y.) -- Politique économique.; Lower East Side (New York, N.Y.) -- Conditions sociales; Lower East Side (New York, N.Y.) -- Conditions économiques.; Administration municipale -- New York (État) -- New York; globalism; POLITICAL SCIENCE -- Public Policy -- Regional Planning; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; City planning; Community development; Community organization; Economic history; Economic policy; Globalization; Municipal government; Political participation; Politics and government; Social conditions; New York (State) -- New York; New York (State) -- New York -- Lower East Side; Stedelijke ontwikkeling; Overheidsbeleid